2020
DOI: 10.1029/2020wr028331
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Hydraulic Tomography in Identifying Boundary Conditions of Groundwater Basins

Abstract: This study investigates the potential of hydraulic tomography (HT) in identifying the boundary conditions of groundwater basins using numerical experiments. The experiment mimics the scenario of groundwater exploitation reduction in a pilot area of groundwater overexploitation control in the North China Plain. In this study, we propose an approach that integrates the HT concept and readily available groundwater monitoring data to identify the constant head and impermeable boundaries by mapping anomalously high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Additionally, we notice that two abnormal “high‐ D zones” appear at the model's upper left and right side boundaries, where the constant head was assigned. These anomalies may indicate the existence of inflow and outflow boundaries (Daranond et al., 2020; Liu et al., 2020; Sun et al., 2013). Flinchum et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, we notice that two abnormal “high‐ D zones” appear at the model's upper left and right side boundaries, where the constant head was assigned. These anomalies may indicate the existence of inflow and outflow boundaries (Daranond et al., 2020; Liu et al., 2020; Sun et al., 2013). Flinchum et al.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Liu et al. (2020) showed that THT yielded a high‐conductivity zone near the boundary if a constant head boundary is used for the actual flux boundary. Interestingly, the THT analysis of this field data confirms their findings, supported by the regional flow map (Flinchum et al., 2018).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies on synthetic HT surveys at the NCP have proven that the feasibility of utilizing head data induced by groundwater exploitation reduction to enhance basin‐scale aquifer characterization (Liu, Yeh, Wang, Hao, et al, 2020), as well as the potential of HT in identifying the boundary conditions of groundwater basins (Daranond et al, 2020; Liu, Yeh, Wang, Song, et al, 2020). However, these studies did not consider the temporal sampling issues and the role of flux data for subsurface characterization.…”
Section: Introductionmentioning
confidence: 99%